DOES THE LOW LEVEL OF DEHYDROEPIANDROSTERONE SULFATE (DHEA-S) INDEPENDENTLY INFLUENCE RISK OF DEATH AT AGE 55 YEARS AND OLDER? - S. A. Shalnova; A. D. Deev; V. A. Metelskaya; A. V. Kapustina; A. E. Imaeva; Yu. A. Balanova; G. A. Muromtseva; M. A. Shkolnikova; V. M. Shkolnikov (Российский кардиологический журнал)
Aim. To investigate on the possible associations of dehydroepiandrosterone sulfate (DHEA-S) levels in blood serum, with cardiovascular diseases (CVD), risk factors (RF) and all-case mortality, as CV mortality, and to assess the specifics.Material and methods. The results analyzed, of the prospective cohort study “Stress, ageing and health”, that included 1876 persons at age 55 years and older. According to the protocol, all participants were assessed on the RF and CVD. Mortality was assessed based on the continuous death registry, with the standard methods. During 8-year observation, 473 deaths registered, including CVD — 286. Statistics was done with SAS software.Results. Mean DHEA-S levels were 1,5 times higher in men than in women. A significant decline of concentration was found with the age, and decrease gradient was 2 times faster in men. Prevalence of the low DHEA-S level in 55 and older was 17,4%, increased from 7,0% among 55-64 y. o. to 46,2% at age 85 and older (p<0,0001). There were no significant relations with ischemic heart disease (CHD), diabetes and chronic heart failure in men and women. Mean level of DHEA-S was significantly higher in male smokers, and prevalence of low DHEA-S levels in male smokers was lower than in non-smokers. Low concentrations of the studied parameter decreased with the raise of compression force in dynamometry. Similarly, C-reactive protein (CRP) and total cholesterol (TC) in the 1st quintile significantly predicted lower level of DHEA-S. Application of the multiple logistic regression made it to evaluate the independent associations of low DHEA-S and RF, similar for both sexes: age, smoking, low dynamometry, cholesterol level outside the 2-4 quintiles, low CRP. In multiple model of prognostic significance of DHEA-S for all-cause mortality and CV mortality in men there were no significant relations (HR 1,13 13 (0,86-1,50), р=0,38; and HR 1,18 (0,84-2,67), р=0,34, respectively). In female cohort, on the contrary, death risk in low DHEA-S was 1,5 times higher, than in higher concentrations (HR 1,58, 95% CI 1,12-2,24, p=0,009). The significance of differences remained with correction for the age, raised BP, CHF, low dynamometry and TC levels outside 2-4 quintiles. For CV mortality in women the low DHEA-S was significant at 9%. Conclusion. Low DHEA-S is independent predictor of all-cause mortality in women 55 years and older, but does not significantly associate with mortality in men of the same age.